2023
DOI: 10.1007/s00405-023-07827-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-based, short-term “neoadjuvant” treatment allows resectability in stage IVB and C anaplastic thyroid cancer

Abstract: Introduction Few available data indicate that a mutation-based “neoadjuvant” therapy in advanced anaplastic thyroid carcinoma (ATC) might convert an initially unresectable primary tumor to resectable and optimize local tumor control. We evaluated a preoperative short-term “neoadjuvant” therapy with a BRAF-directed therapy or, in case of BRAF non-mutated tumors, an mKI/checkpoint inhibitor combination in three patients with ATC stage IVB and C. Methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, due to the highly specialized nature of the treatment of LATC, we recommend the application of a multi-disciplinary team (MDT) model, which uses multidisciplinary assessment to discuss the assessment of tumor resectability and the assessment of physical status prior to neoadjuvant therapy, if it is anticipated that it will be difficult to achieve R0 or R1 resection, or if it will be difficult to preserve the function of the adjacent structures or organs due to a large surgical extent, and the patient is in good physical condition, neoadjuvant therapy can be considered to improve the resection rate of subsequent surgery and the quality of life of patients. Due to the insensitivity of TC to radiotherapy, targeted therapy is currently the main neoadjuvant treatment modality [ 38 ], and targeted therapy plus immunotherapy or chemotherapy can be used for poorly differentiated LATC [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the highly specialized nature of the treatment of LATC, we recommend the application of a multi-disciplinary team (MDT) model, which uses multidisciplinary assessment to discuss the assessment of tumor resectability and the assessment of physical status prior to neoadjuvant therapy, if it is anticipated that it will be difficult to achieve R0 or R1 resection, or if it will be difficult to preserve the function of the adjacent structures or organs due to a large surgical extent, and the patient is in good physical condition, neoadjuvant therapy can be considered to improve the resection rate of subsequent surgery and the quality of life of patients. Due to the insensitivity of TC to radiotherapy, targeted therapy is currently the main neoadjuvant treatment modality [ 38 ], and targeted therapy plus immunotherapy or chemotherapy can be used for poorly differentiated LATC [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two prospective trials are ongoing (DRKS00013336, NCT04171622) [ 18 , 19 ], and we hope to obtain further evidence on the efficacy of lenvatinib and pembrolizumab in treatment-naïve patients and possibly improve patient selection. Additionally, these studies may explore the potential role of the combination therapy in the neoadjuvant setting as it has recently been suggested in two ATC cases [ 20 ].To date, there are no validated biomarkers predicting the effectiveness of lenvatinib and pembrolizumab in ATC. However, Dierks et al found a PD-L1 TPS > 50% or high tumor mutational burden in patients with long-lasting responses [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also a few other reports in which P+L appeared to be effective as salvage treatment in BRAF wild-type cases ( 5 , 6 ). In another report of BRAF wild-type ATC, treatment with P+L was used as an adjuvant, enabling the resection of the lesion (an apparent R0), but the patient relapsed 4 months later ( 8 ). Finally, another study showed some efficacy of treatment with P+L as the first-line therapy (after EBRT) in five patients with ATC.…”
Section: Discussionmentioning
confidence: 99%